2007
DOI: 10.1107/s0021889806049028
|View full text |Cite
|
Sign up to set email alerts
|

An apparatus for electric-field-induced protein crystallization

Abstract: A new device has been fabricated for electric field‐induced protein crystallization with the microbatch method. In conjunction with this, a specialized tray using inexpensive plastic film has been developed for economical set‐up of the experiments. Crystallization can be conducted using AC or DC voltage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 6 publications
0
37
0
Order By: Relevance
“…It is also difficult to control the nucleation process of proteins, and therefore some research that has employed the application of electric fields to protein solutions [17,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] has been actively performed. Almost all of this research used a DC electric field, and it was reported that the nucleation rate for protein crystals decreased.…”
Section: Introductionmentioning
confidence: 99%
“…It is also difficult to control the nucleation process of proteins, and therefore some research that has employed the application of electric fields to protein solutions [17,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] has been actively performed. Almost all of this research used a DC electric field, and it was reported that the nucleation rate for protein crystals decreased.…”
Section: Introductionmentioning
confidence: 99%
“…A growth technique mediated by screw dislocations under low supersaturation has also been proposed [29][30][31][32]. Techniques in which an electric field is applied to a protein solution have also been actively investigated, with a focus on controlling the nucleation rate [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…While applying EFs, there occurs a reduction in the nucleation site numbers, accompanied by a rapid increase in lysozyme crystal size. A method for protein crystallization involving the use of a microbatch under oil (where the crystallizing protein is contained in a small droplet of solution dispensed on electrically isolated electrodes) and a relatively low voltage (30-270 V) has been developed by Al-Haq et al [46].…”
Section: Crystallization In the Presence Of Electric Fields (Efs)mentioning
confidence: 99%